Field notes contributed by Chris Edwards, spring 1997 - Edwards, Chriset al (1997)
List of birds and locations contributed by Chris Edwards. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1997. Epson - sheet feed